PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 011 SIDOREJO KECAMATAN SIMPANG KANAN - Santoso, Budi; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is still lower social studies, social studies learning more centered on the teacher, exercises are given more routine and in the process of student learning more passive. It was seen from the percentage of test scores of students who reach KKM in class IV SDN 011 Sidorejo Simpang Kanan districts is 41.67% of the 12 students with an average value was 63.33. The school is defined KKM 65. From these problems need to be carried out action research with cooperative learning model examples of non examples ". This research aims to improve learning outcomes IPS fourth grade students of SDN 011 Simpang Kanan districts Sidorejo Academic Year 2014/2015. This research was conducted in March until april 2015. The subjects were  fourth grade students of SDN 011 Sidorejo Simpang Kanan districts with the number of students as many as 12 people. This research is a form of classroom action research consisting of 2 cycles. I cycle consists of 2 meetings and the second cycle consists of 2 meetings. Data collection instruments in this research is to test daily tests, observation of student activity sheets and sheets of observations of teacher activity. The average value of student learning outcomes has increased where before action 63.33, an increase in UH I became 70.00 and increased again at UH II became 80.00. The percentage increase of the basic scores to the first cycle of 10.53% and the percentage increase from the first cycle to the second cycle of 14.29%. Mastery learning students in the first cycle yaitun75,00% increase in cycle 2 to 91.67%. The activities of teachers and students during the learning process also increased. Activity Cycle I teachers with an average of 70.83% categorized Enough, increased in the second cycle with an average of 87.50% categorized as good. While the activity of students has increased from the first cycle the average 66.67% with enough categories increased in the second cycle average of 86.11% with the good category. From the above shows that through the implementation of cooperative learning model examples of non examples it can improve learning outcomes IPS fourth grade students of SDN 011 Sidorejo Simpang Kanan districts. Keyword : Cooperative Learning Model Non Examples Examples,  Social Learning Outcomes